2010
DOI: 10.1080/14786430903074771
|View full text |Cite
|
Sign up to set email alerts
|

Strain glass in ferroelastic systems: Premartensitic tweed versus strain glass

Abstract: Cluster-spin glass and ferroelectric relaxors have been observed in defectcontaining ferromagnetic systems and ferroelectric systems, respectively. However, it is unclear whether or not an analogous glass state exists in the physically parallel ferroelastic (or martensitic) systems. In the 1990s, theoretical studies suggested that premartensitic tweed could be viewed as a strain glass. However, there has been no experimental verification of this hypothesis. In this paper, we provide an experimental test of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 30 publications
3
114
0
Order By: Relevance
“…The well-defined orientation relation between the nanodomains is typical of that formed to relax the elastic energy of an invariant plane strain. 28,29 However, some areas of the nanodomain boundaries oriented along the ͗110͘ consisted of planar defects. In order to better observe these features of the nanodomain structure, the lattice image was digitally filtered by selecting all the spots excluding the central spot in FFT using 1.5 nm −1 smooth edge masks and then taken inverse Fourier transformation which is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-defined orientation relation between the nanodomains is typical of that formed to relax the elastic energy of an invariant plane strain. 28,29 However, some areas of the nanodomain boundaries oriented along the ͗110͘ consisted of planar defects. In order to better observe these features of the nanodomain structure, the lattice image was digitally filtered by selecting all the spots excluding the central spot in FFT using 1.5 nm −1 smooth edge masks and then taken inverse Fourier transformation which is presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tweedlike structures are typically found in systems containing nanodomains which have local T lattice structures with a relatively high c/a ratio, such as for example premartensitic 27 and/or strain glass states. 28,29 This observation is perplexing for NBT, as the structure is R ͑a r = 3.96 Å͒ with only a small R angle ͑␣ r = 89.9°͒. 16 To learn more about the polar nanodomains, we performed HRTEM studies.…”
Section: Resultsmentioning
confidence: 99%
“…1-5 nm size, which grow with decreasing temperature and get frozen at about 20-25 nm below T g . Ren et al 35 explained the observed strain glass behavior as a defect induced suppression of long range order, leading to the appearance of dynamic nanodomains whose dynamics freeze at T g . Recently it was argued 18 that in the case of ferroelastic materials domain boundary patterns can evolve glasslike states while the underlying matrix remains fully crystalline, without any defect induced disorder.…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated in a preceding subsection these authors attributed the modulus dip and the IF peak to a local strain glass transition, which was subsequently further investigated by X-rays, electron microscopy, zero-field cooling/field cooling and static stress-strain experiments (Refs. [24][25][26][27][28][29][30][31]35). Their X-ray diffraction patterns are shown in figure 18(a) while the IF and the Young's modulus results (Refs.…”
Section: Alloys Contaminated With Hydrogenmentioning
confidence: 99%